Campaigns, Mobilization, and Turnout in Mayoral Elections. (March 2014) - Holbrook, Thomas M.; Weinschenk, Aaron C.
Research on local turnout has focused on institutions, with little attention devoted to examining the impact of campaigns. Using an original data set containing information from 144 large U.S. cities and 340 separate mayoral elections over time, our contributions to the scholarship in this field are manifold: we focus the literature more squarely on the impact of campaigns by examining the role of campaign effort (measured with campaign expenditures), candidates, and competition in voter mobilization; demonstrate the relative importance of challenger versus incumbent campaign effort in incumbent contests; and show that changes in campaign activities influence changes in turnout over time.